Chronically Elevated O-GlcNAcylation Limits Nitric Oxide Production and Deregulates Specific Pro-Inflammatory Cytokines - Abramowitz, Lara K.; Hanover, John A. (Frontiers in Immunology, 2022)
Inflammation is the immune response to harmful stimuli, including pathogens, damaged cells and toxic compounds. However, uncontrolled inflammation can be detrimental and contribute to numerous chronic inflammatory diseases, such as insulin resistance. At the forefront of this response are macrophages, which sense the local microenvironment to respond with a pro-inflammatory, M1-polarized phenotype, or anti-inflammatory, M2-polarized phenotype. M1 macrophages upregulate factors like pro-inflammatory cytokines, to promote inflammatory signaling, and inducible Nitric Oxide Synthase (iNOS), to produce nitric oxide (NO). The generated NO can kill microorganisms to protect the body, but also signal back to the macrophage to limit pro-inflammatory cytokine production to maintain macrophage homeostasis. Thus, the tight regulation of iNOS in macrophages is critical for the immune system. Here, we investigated how elevation of the nutrient-sensitive posttranslational modification, O-GlcNAc, impacts M1 polarized macrophages. We identified increased gene expression of specific pro-inflammatory cytokines (Il-6, Il-1β, Il-12) when O-GlcNAc cycling was blocked. We further uncovered an interaction between O-GlcNAc and iNOS, with iNOS being an OGT target in vitro. Analysis of M1 polarized bone marrow derived macrophages deficient in the enzyme that removes O-GlcNAc, O-GlcNAcase (OGA), revealed decreased iNOS activity as measured by a reduction in NO release. Further, elevated O-GlcNAc acted on Il-6 expression through the iNOS pathway, as iNOS inhibitior L-NIL raised wildtype Il-6 expression similar to OGA deficient cells but had no further effect on the hyper-O-GlcNAcylated cells. Thus O-GlcNAc contributes to macrophage homeostasis through modulation of iNOS activity.